PENGARUH ELECTRONIC WORD OF MOUTH (EWOM) DAN ATRIBUT PRODUK WISATA TERHADAP KEPUTUSAN BERKUNJUNG GENERASI Z DI KABUPATEN BADUNG - Wikanatha Sagita, Putu Agus; Kusuma Negara, I Made (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2023)
The aim of this research is to identify electronic word of mouth (eWOM) and tourism product attributes on the decision to visit generation z in Badung Regency. Data collection in this research was carried out using observation techniques, interviews, questionnaires and literature study. The data analysis technique used is qualitative descriptive analysis and multiple linear regression analysis. It is hoped that this research can answer assumptions regarding the shift in tourist interest in several tourist attractions in Badung Regency so that it can provide an understanding regarding the form of development and marketing of tourist destinations in the future. The results of this research are the independent variables consisting of the Electronic word of mouth (eWOM) variable (XI), and tourism product attributes (X2), has a significant effect both partially and simultaneously on the dependent variable, namely the decision variable to visit (Y) generation z in Badung Regency with a coefficient of determination of 72.3%.